2016
DOI: 10.1073/pnas.1612322114
|View full text |Cite|
|
Sign up to set email alerts
|

Bax transmembrane domain interacts with prosurvival Bcl-2 proteins in biological membranes

Abstract: The Bcl-2 (B-cell lymphoma 2) protein Bax (Bcl-2 associated X, apoptosis regulator) can commit cells to apoptosis via outer mitochondrial membrane permeabilization. Bax activity is controlled in healthy cells by prosurvival Bcl-2 proteins. C-terminal Bax transmembrane domain interactions were implicated recently in Bax pore formation. Here, we show that the isolated transmembrane domains of Bax, Bcl-x L (B-cell lymphoma-extra large), and Bcl-2 can mediate interactions between Bax and prosurvival proteins insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 60 publications
(69 reference statements)
4
76
2
Order By: Relevance
“…2A. This conclusion is consistent with reports that Bax helix 9 is involved in higher-order oligomer formation (Andreu-Fernandez et al, 2017, Zhang et al, 2015. Importantly, because BaxG179P could permeabilize liposomes almost as well as WT Bax, we conclude that higher-order oligomers are not required for membrane permeabilization.…”
Section: Membrane Pores Can Form and Enlarge In The Absence Of Highersupporting
confidence: 93%
See 1 more Smart Citation
“…2A. This conclusion is consistent with reports that Bax helix 9 is involved in higher-order oligomer formation (Andreu-Fernandez et al, 2017, Zhang et al, 2015. Importantly, because BaxG179P could permeabilize liposomes almost as well as WT Bax, we conclude that higher-order oligomers are not required for membrane permeabilization.…”
Section: Membrane Pores Can Form and Enlarge In The Absence Of Highersupporting
confidence: 93%
“…The laboratory of Jialing Lin (Zhang et al, 2015), identified one mutant, BaxT182I, as being competent in membrane insertion, but defective in higher-order oligomerization (dimer-dimer interaction). Another study showed that the G179P mutation produced a defect in helix 9 interactions, in studies where the helix 9 sequence was joined to a fusion partner (Andreu-Fernandez et al, 2017).…”
Section: Membrane Insertion Of Bax But Not Higher-order Oligomer Formentioning
confidence: 99%
“…Similar experimental approaches were used to confirm the membrane targeting function of the C-terminus, but also suggest that the tail-anchor regions of Bcl-2 family proteins undergo a novel intramembrane dimerization (Andreu-Fernandez et al, 2017; Bleicken et al, 2014) where the C-terminal transmembrane domain, helix α9, of two Bax molecules interact either in parallel or anti-parallel angles within the membrane and away from the apoptotic pore (Bleicken et al, 2014; Iyer et al, 2015; Liao et al, 2016). C-terminal dimer interactions within the mitochondrial membrane were not required for release of small molecules, such as cytochrome c , but were needed to form larger pores, suggesting that these tail-tail interactions are required for pore expansion (Zhang et al, 2016).…”
Section: Impact Of Bcl-2 Family Proteins On Mitochondria-like Membmentioning
confidence: 80%
“…The Bcl-2 is an anti-apoptotic protein that prevents apoptosis by controlling caspases activation or by guarding mitochondrial membrane integrity (Andreu-Fernández et al 2017). Rana (2008) mentioned that the heavy metals and organic solvents in paints induced apoptosis by activation of mitochondrial apoptogenic proteins, then apoptotic signal proceeds and cell death occurs (Roset et al 2007).…”
Section: Discussionmentioning
confidence: 99%